MILITARY EDUCATION AT A NON-MILITARY UNIVERSITY: THE ROAD TO STABILITY - Dmitry A. Endovitsky; Viktor G. Shamaev (Moscow Polytechnic University, 2016)
The article reviews military education formation and development in a non-military university by the example of Voronezh State University. It analyzes the educational activity and specialist training quality provided by the Military Training Centre over a certain period. The authors also discuss the legal and regulatory framework applied in this field.